The composite mean regression as a tool in production studies - Eivind Bjøntegård (University of Oslo, Department of Economics, 1999)
Johansen (1972) explains how a short run macro production function can be derived on the basis of a distribution of micro production units with respect to fixed input coefficients. The present note points out that the composite mean regression, introduced by Frisch (1929), can be useful in analysing some of the production models in Johansen (1972). The focus is on complementary, alternative and marginally independent production factors at the macro level in a production model which assumes efficient allocation of given quantities of inputs.
Keywords: 330; Composite mean regression; complementary; alternative and marginally independent production factors; macro production functions; Regression; Produktionsfunktion; Theorie